Efeito da suplementação de nutrientes e da concentração de permeado de soro de leite no crescimento de Saccharomyces boulardii em sistema descontínuo - Nadai, Barbara Lepretti de (2015)
Whey is considered one of the most polluting waste from the food industry, and its treatment a highly expensive process. An alternative for its reuse is applied to obtain biotechnological products. The objective of this study was to optimize the cell biomass production conditions of S. boulardii yeast in a batch system, using whey permeate. An experimental design was applied DCCR (a central composite design), and in response to cellular biomass, in order to evaluate the effect of four variables on cell biomass response. Fermentations were carried out at different pH, ammonium sulfate concentrations, and permeate. Two experiments with aeration to the fermentation medium were performed, aiming to increase the production of cell biomass. The highest cell biomass obtained in DCCR was 40,06 gL-1, under the following conditions: 7,5 gL-1 of ammonium sulfate, 1,25 gL-1 of magnesium sulfate, 1,5 gL-1 of monobasic potassium phosphate and 180 gL-1 of permeate, 30°C, agitation 100 rpm and pH 5,5. The investigated pH that favored the production of cell biomass was 4,5. The permeate concentrations which favored the production of biomass are included in the range of 180 to 220 gL-1. Thus, the study demonstrated that the whey permeate is a residue having great potential in producing cellular biomass using the yeast S. boulardii, showing how to dispose of this alternative, reducing negative impacts on the environment and decreasing costs for wastewater treatment industries.